Half‐mode substrate integrated waveguide antenna for generating multiple orbital angular momentum modes. Issue 9 (4th April 2016) - Chen, Yiling; Zheng, Shilie; Chi, Hao; Jin, Xiaofeng; Zhang, Xianmin
Abstract : To multiplex multiple orbital angular momentum (OAM) beams, a compact half‐mode substrate integrated waveguide leaky‐wave antenna (LWA) for generating multiple high‐order OAM modes is presented. The LWA is based on a cavity resonator with two feeds of ±90° phase difference. The principle and mode analysis of the resonator are discussed, and the generation of high‐order OAM beams is proved by the measurements.